Nodular fasciitis in the forehead: a rare presentation - Montalvão, Patrícia Pinheiro; Teixeira, Amanda Soares; Michels, Isadora Barreto; Gioppo, Ingrid Stresser; Miola, Anna Carolina [UNESP] (GN1 Sistemas e Publicacoes, 2020)
Nodular fasciitis is a benign tumor resulting from the reactive proliferation of fibroblastic or myofibroblastic cells presenting rapid growth and rich cellularity. In adults, the extremities’ involvement is more frequent; however, other regions can be affected. In this report, we present the case of a 40-year-old woman with a nodular lesion on the forehead. The histopathology confirmed the diagnosis of nodular fasciitis. The reported case highlights its rare location and alerts the clinical dermatologist in its inclusion among the differential diagnoses of tumor lesions on the face.
Fasciite nodular na fronte: uma rara apresentação
Keywords: Facial Dermatoses; Fasciitis; Forehead